Pengaruh Price Earning Ratio, Laba Per Saham, Return On Assets & Return On Equity Terhadap Harga Saham Perbankan Terdaftar Di BEI - Talamati, Mohamad Rianto (JURNAL RISET BISNIS DAN MANAJEMEN, 2018)
The purpose of this research is to analyze the influence of Price Earning Ratio, Profit per Share, Return on Assets & Return on Equity to banking in Indonesia Stock Exchange in year 2012-2016. The sample used is 27 banking companies that passed the purposive sampling test. The correlation coefficient (R) shows the variables having a strong relationship. The coefficient of determination shows that Stock Price is affected by Income per Share and Return on Equity. Simultaneously, the variable Price Earning Ratio, Earnings per Share, Return on Assets & Return on Equity affect the price of banking shares listed on the Indonesia Stock Exchange. Partially, Price Earning Ratio and Earnings per Share have a significant positive effect on Stock Price while Retun on Assets & Return on Equity has a partially insignificant effect on Banking Share Price listed on Indonesia Stock ExchangeKeywords: Price Earning Ratio, EPS, Return on Assets, Return on Equity, Stock Price.